Quantitative methods to monitor RNA biomarkers in myotonic dystrophy - Wojciechowska, Marzena; Sobczak, Krzysztof; Kozlowski, Piotr; Sedehizadeh, Saam; Wojtkowiak-Szlachcic, Agnieszka; Czubak, Karol; Markus, Robert; Lusakowska, Anna; Kaminska, Anna; Brook, J. David (Nature Publishing Group, 2018)
Myotonic dystrophy type 1 (DM1) and type 2 (DM2) are human neuromuscular disorders associated with mutations of simple repetitive sequences in afected genes. The abnormal expansion of CTG repeats in the 3′-UTR of the DMPK gene elicits DM1, whereas elongated CCTG repeats in intron 1 of ZNF9/CNBP triggers DM2. Pathogenesis of both disorders is manifested by nuclear retention of expanded repeat containing RNAs and aberrant alternative splicing. The precise determination of absolute numbers of mutant RNA molecules is important for a better understanding of disease complexity and for accurate evaluation of the efficacy of therapeutic drugs. We present two quantitative methods, Multiplex Ligation-Dependent Probe Amplifcation and droplet digital PCR, for studying the mutant DMPK transcript (DMPKexpRNA) and the aberrant alternative splicing in DM1 and DM2 human tissues and cells. We demonstrate that in DM1, the DMPKexpRNA is detected in higher copy number than its normal counterpart. Moreover, the absolute number of the mutant transcript indicates its low abundance with only a few copies per cell in DM1 fibroblasts. Most importantly, in conjunction with fuorescence in-situ hybridization experiments, our results suggest that in DM1 fibroblasts, the vast majority of nuclear RNA foci consist of a few molecules of DMPKexpRNA.